Generic skills development and learning/assessment process: Use of rubrics and students validation - Montserrat Iborra Urios; Eliana Ramírez Rangel; Roger Bringué Tomàs; Javier Tejero Salvador; Fidel Cunill García; Carles Fité Piquer (OmniaScience, 2015)
To fulfil the European Higher Education context in the subject of the Chemical Engineering Undergraduate Degree of University of Barcelona named "Chemical Engineering Experimentation II", team work, written and oral communication generic skills were developed and assessed by means of rubrics. In order to appraise the methodological usefulness of rubrics to formative/summative assessment, rubrics validation was done by students. Rubrics were employed for several learning/assessment activities and the students' perception about the teaching/learning process was collected, analysed and compared to the academic marks.